2009
DOI: 10.1007/s00128-009-9832-3
|View full text |Cite
|
Sign up to set email alerts
|

PCDD/Fs and Dioxin-Like PCBs in Sediments from Yellow Estuary and Yangtze Estuary, China

Abstract: Twenty one surface sediments were analyzed for PCDD/Fs and dioxin-like PCBs by HRGC-HRMS in Yellow Estuary and Yangtze Estuary in China. The concentration ranges of 2,3,7,8-substituted PCDD/Fs, dioxinlike PCBs and WHO-TEQ were 2.33-253, 0.04-139 and 0.11-1.01 pg/g dw respectively in sediment from two estuaries. For PCDD/Fs and dioxin-like PCBs, OCDD, CB77, CB105 and CB118 were found to be dominant. The pollution levels in two estuaries were lower compared with that in other locations reported by previous studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 17 publications
4
10
1
Order By: Relevance
“…The concentrations of PCDD/Fs in sediments of the Daliao River Estuary were similar to those in the Yongdingxin River Estuary , Yellow River Estuary (Hui et al, 2009); but were lower than those in sediments from the Haihe River Estuary and Dagu Drainage River Mouth (Hu et al, 2005;Liu et al, 2007). The PCB levels in our present study were much higher than those in the Yongdingxin River Estuary and Yellow River Estuary (Hui et al, 2009), similar to Haihe River Estuary , but lower than those in the high pollution area, namely the Dagu Drainage River Mouth.…”
Section: Pollution Status Of Pcdd/fs Pcbs and Pcnssupporting
confidence: 61%
“…The concentrations of PCDD/Fs in sediments of the Daliao River Estuary were similar to those in the Yongdingxin River Estuary , Yellow River Estuary (Hui et al, 2009); but were lower than those in sediments from the Haihe River Estuary and Dagu Drainage River Mouth (Hu et al, 2005;Liu et al, 2007). The PCB levels in our present study were much higher than those in the Yongdingxin River Estuary and Yellow River Estuary (Hui et al, 2009), similar to Haihe River Estuary , but lower than those in the high pollution area, namely the Dagu Drainage River Mouth.…”
Section: Pollution Status Of Pcdd/fs Pcbs and Pcnssupporting
confidence: 61%
“…As expected, the PCDD/Fs TEQ concentrations in the four sediment samples from Bohai Bay (BH1eBH4) ranged from 8.4 to 58.7 pg WHO-TEQ/g dw with a mean value of 27.1 pg WHO-TEQ/g dw. These concentrations are higher than those measured at the Qingdao Coastal Sea (0.2e4.2 pg/g TEQ dw) (Pan et al, 2008), and the Yellow River and Yangtze River estuaries (0.11e1.01 WHO-TEQ pg/g) (Hui et al, 2009) in China. Similar congener profiles were found in the river sediment and Bohai Bay sediment samples, suggesting that the PCDD/F concentrations in Bohai Bay are contributed by this contaminated site.…”
Section: Concentrations and Distribution Of Pcdd/fs In Soils And Sedicontrasting
confidence: 54%
“…Bao et al (1995) reported that OCDD contributed 76% to the Liu et al (2008) reported that OCDD was the predominant congener and that RPCDD concentrations were higher than RPCDF concentrations in water from the Xijiang River, China. OCDD, HpCDD, and OCDF have been found to be the main PCDD/F homologs in sediments from the Yangtze and Yellow Rivers (Hui et al, 2009). The PCDD/F congener profiles found in sediments from the Haihe River, the Dagu Drainage River (Liu et al, 2007), and Taihu Lake (Zhang and Jiang, 2005) also agreed well with the results of this study.…”
Section: Pcdd/fs In Watersupporting
confidence: 89%